Ethylene vinyl acetate (Eva) nanocomposites incorporating hybrid nanofillers for biomedical applications) - Goh, Khung Weng (School of Material Engineering, University Malaysia Perlis, 2016)
Ethyl vinyl acetate (EVA) copolymers possess exceptional mechanical properties, barrier properties and biocompatibility, thus they are potentially to become as materials for biomedical applications. In this research, neat EVA incorporating with the organically modified montmorillonite/bentonite (OMMT/Bent) hybrid nanofiller in different ratio (3:0, 2.75:0.25, 2.5:0.5, 2.25:0.75, 2:1 and 0:3 in wt. %) were prepared by z-blade mixer at 50 r.p.m. and 175 , compressed into 1 mm sheet at 10 atm. and 160 . The morphology of the neat EVA, EVA nanocomposites and EVA hybrid nanocomposites was investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR). The biostability of these materials was analysed by comparing the percent reduction of tensile strength upon the in vitro exposure (4 weeks of immersion in PBS solution at 37 ), the FTIR spectrum and SEM characteristics before and after the in vitro exposure. The better filler dispersion of OMMT/Bent nanofillers than control Bent nanofillers was observed by TEM. Except for EVAO2B1, all the EVA/OMMT/Bent hybrid nanocomposites show statistically no different its ambient and in vitro tensile properties by comparing with neat EVA. EVAO2.75B0.25 had achieved the least reduction in mechanical properties upon 4 weeks exposed to phosphate buffered saline (PBS) solution at 37 . Furthermore, the results from SEM and FTIR had strongly proven the improvement in biostability with the addition of O2.75B0.25 hybrid nanofiller into EVA matrix. The obtained results indicate that the potential of using the hybrid OMMT/Bent nanofiller for biostability enhancement of the EVA and reducing the costs of EVA nanocomposites production by using less expensive Bent as co-filler with the OMMT.